‘Firearming’ Fairytales: NRA and Gun Culture in American Fan-Fiction - Bhakti Satrio Nugroho (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2022)
Gun issue becomes one of the most polemic issues in the United States alongside racism. Regardless, the last major gun control legislation to make it into law was the assault weapons ban in 1994 as part of a larger crime-related bill approved during Bill Clinton presidential period. After the assault weapons ban expired, American society is threatened by the increasing numbers of gun violence issue such as mass shooting and gun homicide. In this case, NRA involvement is vital towards gun culture in the United States. As non-profit organization, NRA has influential lobbying for any policies towards gun policies. Thus, this paper discusses the dissemination of gun culture on NRA family website www.nrafamily.org. In 2016, Amelia Hamilton rewrote two Grimm’s fairytales “Little Red Riding Hood (Has a Gun)” and “Hansel and Gretel (Have Guns). Since gun becomes commodity, these NRA versions of fairytales can be analyzed as part of consumer manipulation by using consumer capitalist theory. Thus, this analysis shows that those fan-fictionalized fairytales consist of two main aspects: gun as protector and gun culture as common culture in the United States. It embraces the rationalization of gun ownership’ in the United States despite its lethal consequences.